Water-Holding Property Of Sodium Hyaluronate - TONOOKA, Noriaki (Skin research, 1985)
From its chemical structure, it was speculated that sodium hyaluronate (HA) would have some interesting properties suitable for cosmetic applications.The physical properties of this natural polymer have been investigated by physicochemical techniques. 1.Water-absorbing and water-holding tests HA was less water-absorbing than sodium pyrrolidone carboxylate and glycerine but more water-holding than glycerine and sorbitol.Accordingly, it was concluded that HA would be a more effective moisturizer than lowmolecular water-holding agents now widely used in cosmetics. 2.Film strength and elasticity tests Various films which were derived from watersolube polymers such as HA, polyvinyl alcohol, and polypeptide tested by stretching apparatus. Each sample gave complex result under each humidity condition.Of the samples tested, HA gave the highest values of strength and elasticity under all test conditions. 3.Surface slipping resistance tests For detecting enhanced smoothness due to the application of water-soluble polymers on the sIip resistance, values were measured with the slip restance instrument.Smoothing effect was clearly detected with HA but not with polypeptide or sodium chondroitin sulfate. Further investigation had been out on its sensory effect in practical use on 353 subjects. HA is a useful and desirable material in cosmetic field, partic ularly as a moisturizing agent with forming an elasic film water-holded on skin surface.